Correlation of tests used in Comprehensive Geriatric Assessment. Systematic Review - Radosław Perkowski; Joanna Androsiuk; Agnieszka Kujawska; Małgorzata Gajos; Paulina Kasperska; Weronika Topka; Katarzyna Mądra-Gackowska; Ewelina Romanowska; Sylwia Płusa; Tomasz Aleksiewicz; Marcin Kożuchowski; Piotr Biegański; et al. (Kazimierz Wielki University, 2016)
Perkowski Radosław, Androsiuk Joanna, Kujawska Agnieszka, Gajos Małgorzata, Kasperska Paulina, Topka Weronika, Mądra-Gackowska Katarzyna, Romanowska Ewelina, Płusa Sylwia, Aleksiewicz Tomasz, Kożuchowski Marcin, Biegański Piotr, Główczewska-Siedlecka Emilia. Correlation of tests used in Comprehensive Geriatric Assessment. Systematic Review. Journal of Education, Health and Sport. 2016;6(7):207-217. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.57337 http://ojs.ukw.edu.pl/index.php/johs/article/view/3686       The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.06.2016. Revised 09.07.2016. Accepted: 09.07.2016.     Correlation of tests used in Comprehensive Geriatric Assessment. Systematic Review   Radosław Perkowski1, Joanna Androsiuk1, Agnieszka Kujawska1, Małgorzata Gajos1, Paulina Kasperska1, Weronika Topka1, Katarzyna Mądra-Gackowska1, Ewelina Romanowska1, Sylwia Płusa1, Tomasz Aleksiewicz1, Marcin Kożuchowski1, Piotr Biegański2, Emilia Główczewska-Siedlecka1   1. Katedra i Klinika Geriatrii, Wydział Nauk o Zdrowiu, Collegium Medicum UMK w Bydgoszczy 2. Katedra Higieny, Epidemiologii i Ergonomii, Zakład Ergonomii i Fizjologii Wysiłku Fizycznego   Abstract Comprehensive Geriatric Assessment (CGA) has been used in clinics for almost 100 years. It includes holistic approach to patients examination. In this systematic review we analyzed results of tests used in CGA and correlation of results. Moreover, we underlined some issues concerning homogeneity of tests used in CGA as well as scientific validity of some of its tools. Results of prospective studies show that some of results of examination used in CGA are good predictors of functioning in another health domain in next years. Systolic blood pressure as well as BMI could be good predictors for neuropsychological functioning, however results are equivocal. Low scores in dual task (walking and cognitive engaging task simultaneously) are good predictor for falls occurrence. Education measured by socioeconomic status is very often mentioned as one of the best predictors of cognitive functioning. Undergoing Mini Nutritional Assessment by patients could be an effective tool to improve their nutrition status, possibly by indirectly influencing on their diet habits. Moreover, genotype examination could be worth to include into CGA due to, inter alia, examination of possible causes of dietary deficits. Aerobic examination could be done by cost-free tests, which sensitivity and specify are on tolerable level. It could help lowering CGA costs, which will help make it widely available for patients.   Keywords: Comprehensive Geriatric Assessment, cognitive functioning, older people.